PERAN MEDIASI PEMBERDAYAAN PADA PENGARUH STRES KERJA DAN KONFLIK PEKERJAAN-KELUARGA TERHADAP KOMITMEN PROFESIONAL - Kepakisan, I Gst Ngr Bgs Bimantara; Supartha, Wayan Gede; Dewi, I Gusti Ayu Manuati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.05.TAHUN 2018, 2018)
This study aims to examine the role of empowerment in mediating the influence of work stress and work-family conflict to professional commitment of employees at PT. Bhineka Putra Perkasa. This research was conducted at PT. Bhineka Putra Perkasa located on  Denpasar. The number of samples was 52 respondents taken using slovin method. Data were tested using path analysis techniques. The result of the analysis shows that job stress has negative effect on empowerment. Work-family conflicts negatively affect empowerment, job stress negatively affects employee professional commitment and work-family conflicts negatively affect employees' professional commitments. Empowerment positively affects employees' professional commitment. Empowerment mediates the effect of job stress on employee professional commitment and mediates the impact of work-family conflicts on employee professional commitments. Suggestions for recommended companies are required to act with integrity, through consistency by choosing and placing employees according to their ability and knowledge to avoid work conflicts. Acting firmly in fostering employees so as to have a good sense of cooperation to reduce stress levels in work .